2015
DOI: 10.1097/pcc.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Longer RBC Storage Duration Is Associated With Increased Postoperative Infections in Pediatric Cardiac Surgery

Abstract: Background Infants and children undergoing open heart surgery routinely require multiple red blood cell (RBC) transfusions. Children receiving greater numbers of RBC transfusions have increased post-operative complications and mortality. Longer RBC storage age is also associated with increased morbidity and mortality in critically ill children. Whether the association of increased transfusions and worse outcomes can be ameliorated by use of fresh RBCs in pediatric cardiac surgery for congenital heart disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
(37 reference statements)
3
44
1
2
Order By: Relevance
“…For example, observational data have suggested that infection rates are strikingly higher in infants and children undergoing cardiac surgery who receive washed transfusions of older RBCs (25-38 days). 57 Researchers found that washing the RBCs that were oldest (eg, .29 days) was related to an increase in morbidity when compared with unwashed RBCs. 57 An individual patient meta-analysis from studies that enrolled infants and small children who received very large volumes of washed RBCs may be a feasible approach to explore these issues.…”
Section: Strengths and Concerns/limitationsmentioning
confidence: 99%
“…For example, observational data have suggested that infection rates are strikingly higher in infants and children undergoing cardiac surgery who receive washed transfusions of older RBCs (25-38 days). 57 Researchers found that washing the RBCs that were oldest (eg, .29 days) was related to an increase in morbidity when compared with unwashed RBCs. 57 An individual patient meta-analysis from studies that enrolled infants and small children who received very large volumes of washed RBCs may be a feasible approach to explore these issues.…”
Section: Strengths and Concerns/limitationsmentioning
confidence: 99%
“…Observational studies have demonstrated an increased risk associated with red cell transfusions (9)(10)(11). This risk seems to be related to both the age and number of the units transfused.…”
mentioning
confidence: 99%
“…A higher rate of postoperative infections when RBCs older than 25 days were transfused was also detected in a trial focused on pediatric cardiac surgery. 32 In contrast, two other studies found that a storage age of RBC transfusion up to 21 to 35 days was not correlated with increased postoperative adverse events in patients undergoing cardiac surgery. 6,29 Interestingly, the cutoff used to define fresh or old blood ranged from 14 to 25 days, resulting in high heterogeneity between studies and, consequently, a difficult comparison of results.…”
Section: Subgroup Analysismentioning
confidence: 73%
“…A higher rate of postoperative infections when RBCs older than 25 days were transfused was also detected in a trial focused on pediatric cardiac surgery. 32 In contrast, two other studies found that a storage age of RBC transfusion up to 21 to 35 days was not correlated with increased postoperative adverse events in patients undergoing cardiac surgery. …”
mentioning
confidence: 73%